The Effect of Oral Potentially Malignant Disorders (OPMD) on Dental Implants Survival—A Systematic Review - Sebahat Kaya; Christian Walter; Aya Khamis; Lena Katharina Müller-Heupt; Stefanie Zimmer; Lorena Cascant Ortolano; Keyvan Sagheb; Bilal Al-Nawas; Eik Schiegnitz (Dentistry Journal)
Objectives: This research is purposed to synthesize the existing evidence on implant survival rates in patients with oral potentially malignant disorders (OPMD) and assess potential risk factors associated with peri-implant disease. Material and Methods: A comprehensive search was performed across PubMed MEDLINE, Cochrane Library, and Web of Science. This review was conducted according to the PRISMA guidelines, including studies published between 2012 and 2023. Results: The review of studies related to oral lichen planus (OLP) revealed an implant survival rate of 99.3% (50% to 100%) with a mean follow-up of 40.1 months. One retrospective study focused on patients with leukoplakia and erythroplakia, but did not provide data on implant survival; however, it reported the presence of oral squamous cell carcinomas (OSCC) in the vicinity of dental implants. Data from a patient with proliferative verrucous leukoplakia (PVL) indicated a 100% implant survival rate, while patients with systemic lupus erythematosus (SLE) showed an implant survival rate of 97.67%. For all other entities of OPMD no articles could be found. Conclusions: With the exception of OLP, there is a limited number of studies or none on all other entities of OPMD. The available literature indicates no impact of OLP on implant survival rates and does not support OLP as a risk factor for peri-implant disease. For the other entities of OPMD, no conclusion regarding implant survival or peri-implant disease risk factors can be drawn due to a lack of studies. To validate the results and evaluate OPMD on peri-implant tissue, large-scale prospective studies for all types of OPMD, especially for leukoplakia and erythroplakia, are needed.